A COMPARATIVE STUDY OF FULL MOUTH BLEEDING SCORE (FMBS) AND GINGIVAL INDEX LOE AND SILNESS (GILS) IN ASSESSING GINGIVAL STATUS OF CHILDREN AGED 10-14 YEARS - Hristina Tankova; Zornitsa Lazarova (Peytchinski Publishing, 2024)
Aim: Comparative analysis of two gingival indices with different diagnostic thresholds and methods of application in recording the gingival status of the whole dentition in children aged 10-14 years. Materials and methods: The subjects of the current study were 457 children. The clinical periodontal examination is performed in 4 levels. Gingival status is objectified by inspection and probing using (1) provoked gingival bleeding by the full mouth bleeding score (FMBS) with a diagnostic threshold above 10% bleeding gingival units and (2) gingival index according to Loe and Silness (GILS), with a diagnostic threshold above 0. Results: Gingival inflammation could be detected in 64.3% of the children studied, with a mild form of plaque-induced gingivitis in 40% of them, concentrated mainly on the vestibular surfaces in the frontal regions of both jaws. In 87% of the same children studied, we recorded an initial degree of gingival inflammation with a gingival GILS index value above 0, also concentrated in the frontal areas of both dental arches.